Mencari Teater Modern Indonesia Versi Asrul Sani: Penelusuran Pascakolonial - Darwis, Taufik (PANGGUNG, 2013)
ABSTRACTÃÂ Asrul Sani, along with Chairil Anwar and Rivai Apin, may sound familiar and renowned in literaÃÂ ture, in spite of theatre, as one of the major literary figures of Angkatan Ã¢â¬â¢45. Asrul SaniÃ¢â¬â¢s name might be known widely by the theatre activists and actors only as a translator. His name is observed because it is often cited in the translated drama text which is selected to be played. Those who are more observant and seriously wanted to explore their ability in acting will also find his name in the elderly book about acting methodology belongs to one of the Russian theatrical figures Ã¢â¬â again as a translator. Perhaps, we are practically unconcern about why his name is frequently cited as a transÃÂ lator in dramatic literature and our theatre, because we never seem to have dispute with the practice of translation itself. Therefore, the writing is directed to investigate and discover the substance that become the fundamental of his idea in the translation practice, and biographically, to disclose Asrul SaniÃ¢â¬â¢s influence (his consideration) toward the development of Indonesian theatre nowadays.ÃÂ Key words: Indonesian modern theater, postcolonialÃÂ ÃÂ ABSTRAKÃÂ Asrul Sani, sama seperti Chairil Anwar dan Rivai Apin, mungkin terdengar tidak asing dan sangat terkenal dalam bidang sastra, selain teater, sebagai salah satu tokoh sastra uta- ma dari Angkatan Ã¢â¬Ë45. Nama Asrul Sani mungkin dikenal secara luas oleh para aktivis teater dan para aktor hanya sebagai penerjemah. Namanya diperhatikan karena sering dikutip dalam teks drama terjemahan terpilih untuk dimainkan. Mereka yang lebih jeli dan secara serius ingin mengeksplorasi kemampuan mereka dalam berakting juga akan mendapatkan namanya dalam buku tua tentang metodologi akting milik salah seorang tokoh teater Rusia - juga sebagai penerjemah. Mungkin, secara praktis kita tidak peduli me- ngapa namanya sering disebut sebagai penerjemah dalam literatur drama dan teater kita, karena tampaknya kita tidak pernah melakukan perdebatan dengan praktek penerjemahan itu sendiri. Oleh karena itu, penulisan ini diarahkan untuk menyelidiki dan menemukan substansi yang menjadi dasar idenya dalam praktek penerjemahan, dan secara biografis, untuk mengungkap pengaruh (pertimbangan) Asrul Sani terhadap perkembangan teater di Indonesia saat ini.ÃÂ Kata kunci: Teater modern Indonesia, pascakolonial